2019
DOI: 10.1111/ijlh.12995
|View full text |Cite
|
Sign up to set email alerts
|

Update on diagnostic testing for platelet function disorders: What is practical and useful?

Abstract: Introduction Platelet function disorders (PFD) are an important group of bleeding disorders that require validated and practical laboratory strategies for diagnosis. Methods This review summarizes the authors’ experiences, current literature, and an international survey to evaluate the practices of diagnostic laboratories that offer tests for PFD. Results Blood counts, blood film review, and aggregation tests are the most commonly performed investigations for PFD and help determine whether there is thrombocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…It detects abnormalities associated with increased bleeding in a significant proportion of individuals referred for CPDF assessment. 8 This assay analyzes in vitro platelet aggregation in a GPIIb/IIIa-dependent manner by measuring the increased light transmission through dense PRP after addition of exogenous soluble activators except ristocetin. Ristocetin causes the binding of VWF to the GPIb complex leading to platelet agglutination.…”
Section: Light Transmission Platelet Aggregationmentioning
confidence: 99%
“…It detects abnormalities associated with increased bleeding in a significant proportion of individuals referred for CPDF assessment. 8 This assay analyzes in vitro platelet aggregation in a GPIIb/IIIa-dependent manner by measuring the increased light transmission through dense PRP after addition of exogenous soluble activators except ristocetin. Ristocetin causes the binding of VWF to the GPIb complex leading to platelet agglutination.…”
Section: Light Transmission Platelet Aggregationmentioning
confidence: 99%
“…A recent survey of diagnostic laboratories on inherited platelet dysfunctions found that most laboratories perform LTA. This test has good performance characteristics and detects abnormalities associated with increased bleeding in a significant proportion of individuals referred for platelet function disorder (PFD) investigations [4]. LTA is typically used as a first-line test to guide diagnosis of PFD.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 However, platelet activation also induces initiation and progression of atherosclerosis by several mechanisms, including adhesion, subsequent monocyte recruitment to the endothelium, and induction of proinflammatory mediators. 6 10 Many studies have shown that oxLDL is a causative substance in development of cardiovascular disease (CVD) by promoting activation and aggregation of platelets. 2 , 11 13 However, low oxLDL levels attenuate platelet function and aggregation in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…However, LTA is not ideal for diagnosing thrombosis and determining the effects of antiplatelet drugs because of the complicated test process, including many types of agonists, a low sensitivity, and a lack of standardization. 9 …”
Section: Introductionmentioning
confidence: 99%